2017
DOI: 10.24865/ajas.v2i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Tindak Tutur Direktif Guru Dalam Pembelajaran Bahasa Arab

Abstract: This research investigates teachers' directive speech act in Arabic Language Teaching. The research was applied through pragmatic approach using the theory of Bach and Harnish's speech act and Yule's speech act strategy. The research instrument is in the form of teachers' speech containing directive meaning. Based on the analysis, it can be concluded that: (1) first, the category of teacher's directive speech act in Arabic language teaching at MAN 1 Jombang involves requesting, advising, commanding, challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
9
0
7
Order By: Relevance
“…Analisis tersebut memiliki kesamaan dengan analisis yang dilakukan oleh Qomariyah (2017). Kesamaan tersebut adalah selain sama-sama menginformasikan sesuatu, keduanya juga memiliki fungsi mengajak.…”
Section: Konteks Tuturanunclassified
“…Analisis tersebut memiliki kesamaan dengan analisis yang dilakukan oleh Qomariyah (2017). Kesamaan tersebut adalah selain sama-sama menginformasikan sesuatu, keduanya juga memiliki fungsi mengajak.…”
Section: Konteks Tuturanunclassified
“…Data utterances (9) are speeches which contain directive speech acts of limiting. The saying "this film is presented to those of you who are 17 and above" is a lingual marker that displays a limit age for passengers who want to wacth the film.…”
Section: Speech Formmentioning
confidence: 99%
“…Regarding the use of directive speech act on the sea transportation, there are a number of previous studies that have examined the concept of directive speech acts. The research conducted by Sumiatun [7] entitled "Teacher and Student Directive Speech Acts in Learning in Third Grade Tipo Palu SDN", Safar [8] entitled "Directive Speech Acts in The Transactions Sale at The Central Market of Watampone", and Qomariyah [9] entitled "Directive speech (TTD) of Teachers in Learning Arabic". The three studies have the same focus of discussion which is describing the form, the function of the directive speech act that occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech acts and speech events are two symptoms found in a communication process in conveying or mentioning one intention by the speaker. Hymes in [3] uses the term speech event for activities that are directly regulated by norms in conversation. Hymes also revealed that the speech event has a close relationship with the setting of the event.…”
Section: Introductionmentioning
confidence: 99%